2018
DOI: 10.1177/0042085918801438
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Methods Study of Teacher Dispositions and Culturally Relevant Teaching

Abstract: The study tests the proposition that pedagogical orientations foster domain-specific teacher dispositions. Nineteen preservice teachers in an urban teacher certification program emphasizing culturally relevant teaching (CRT) were interviewed at the completion of all coursework and teaching experiences in diverse, urban classrooms. Dispositional statements ( n = 405) were used in a comparative analysis that included cross-tabs chi-square statistics and contingency tables. The study found that teaching dispositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The teachers interviewed have a positive perception of cultural diversity, but it does not correspond to adequate intercultural educational actions with their students. They admit that it is necessary to develop actions that favour the integration of immigrant students and the participation of parents; they know that these actions are positive for intercultural coexistence [40,51,58]. However, the teachers interviewed from the outset recognize a series of obstacles: they do not have a command of the language, they are unaware of the student's culture, they do not have intercultural resources and materials for the various cultural groups, they think that the students have poor previous academic knowledge acquired in their countries of origin, they have unusual obligations for their age, such as taking care of their siblings and the house, they spend too much time alone at home or on the street, they experience poverty at home...…”
Section: Discussionmentioning
confidence: 99%
“…The teachers interviewed have a positive perception of cultural diversity, but it does not correspond to adequate intercultural educational actions with their students. They admit that it is necessary to develop actions that favour the integration of immigrant students and the participation of parents; they know that these actions are positive for intercultural coexistence [40,51,58]. However, the teachers interviewed from the outset recognize a series of obstacles: they do not have a command of the language, they are unaware of the student's culture, they do not have intercultural resources and materials for the various cultural groups, they think that the students have poor previous academic knowledge acquired in their countries of origin, they have unusual obligations for their age, such as taking care of their siblings and the house, they spend too much time alone at home or on the street, they experience poverty at home...…”
Section: Discussionmentioning
confidence: 99%
“…These include sociocultural awareness, affirming attitudes towards all students, the commitment to act as an agent of change, learning about all students, and the use of CRT practices in teacher education programmes. Truscott and Stenhouse (2018) found that teaching dispositions were associated with academic success and cultural competence. These dispositions were associated with the critical consciousness domain to a minimal extent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This call to attend to teacher bias while attending to the diverse needs of students has been explored through research to inform teacher preparation programs. Scholars such as Truscott and Stenhouse (2018) examine preservice teachers' dispositional shift in a program that emphasizes culturally relevant pedagogy. The outcome of their work suggests an integrated approach (i.e., focusing on CRT throughout the program) to shift dispositions that embrace student diversity.…”
Section: Reinvigorating Teacher Educationmentioning
confidence: 99%